Resposta :
I) Transformação da velocidade, de km/h para m/s:
I.1) V(i):
3,6 km/h ===============> 1 m/s
72 km/h ================> x m/s
3,6 . x = 72 . 1
3,6x = 72
x = 72/3,6
x = 20 m/s
I.2) V(f):
3,6 km/h ==============> 1 m/s
36 km/h ===============> y m/s
3,6 . y = 36 . 1
3,6y = 36
y = 36/3,6
y = 10 m/s
II) Finalmente, aplicando a fórmula da energia cinética:
τ = E(c)f - E(c)i
τ = 1/2 . m . v(f)² - 1/2 . m . v(i)²
τ = 1/2 . 1000 . 10² - 1/2 . 1000 . 20²
τ = 1/2 . 1000 . 100 - 1/2 . 1000 . 400
τ = 50 000 - 200 000
τ = |-150 000| = 150 000 J
Resposta: alternativa C